The electronic detail of a digital pH-meter - De Lucena, Samuel E. [UNESP] (My University, 2006)
This paperwork presents the complete circuitry used to build a microcontroller-based pH-meter. Key control software is also discussed. An industry-standard glass combination electrode has been employed for pH detection. Electrode parameter extraction procedure is presented. Good measurement results, with 1 % error, have been attained. Copyright© (2006) by the International Measurement Federation (IMEKO).
Keywords: PH electrodes; PH measurement; PH-meter; Key control; Measurement results; Microcontroller-based; pH detection; pH Electrode; PH measurements; Glass industry; Parameter extraction; Planning; Sustainable development; Units of measurement; pH effects